Do international acquisitions increase profits? Evidence from the M&A of Italian companies between 2004 and 2015 - Beltratti, Andrea (Piccola Impresa / Small Business, 2019)
We use a new sample including 1,371 Italian firms between 2003 and 2015 in order to study the impact of M&A activity on the EBITDA margin. Using an econometric methodology (propensity score matching) that is robust to the presence of inverse causality, we find that the Italian firms characterized by international M&A operations have a larger sector-corrected EBITDA margin than firms that have put in place domestic M&A operations or firms that do not have put in place any M&A activity at all. International expansion put in place through the purchase of production units has a larger impact on EBITDA margin than international expansion regarding the purchase of distribution networks.